Impact of Selected Serum Factors on Metastatic Potential of Gastric Cancer Cells - Marta Tkacz; Maciej Tarnowski; Agata Poniewierska-Baran; Karol Serwin; Anna Madej-Michniewicz; Anna Deskur; Bogusław Czerny; Teresa Starzyńska (Diagnostics, 2022)
(1) Background: stromal-derived factor-1 (SDF-1/CXCL12), hepatocyte and vascular-endothelial growth factors (HGF and VEGF) have been shown to facilitate cell motility, proliferation and promote local tumor progression and metastatic spread. Recent research shows the important role of these cytokines in gastric cancer (GC) progression. (2) Methods: 21 gastric cancer patients and 19 healthy controls were included in the study. SDF-1, HGF and VEGF levels were evaluated in sera by ELISA. Patients and control sera were used to stimulate CRL-1739 GC cell line, and chemotaxis, adhesion and proliferation potential were assessed. (3) Results: Concentrations of SDF-1, HGF and VEGF were significantly higher in patients than in controls. Chemotaxis and adhesion assays revealed a significant response of GC cells to patients’ serum. Furthermore, significant relationships were seen between chemotactic/adhesion response and tumor stage. Serum from intestinal early GC patients produced significantly stronger chemotactic response when compared to patients with metastatic spread. In turn, serum from patients with distal metastases significantly increased the adhesion of GC cells when compared to sera from the patients with no distal metastases. We also observed that HGF strongly stimulated the proliferation of CRL-1739 cells. (4) Conclusions: We observed that the sera from GC patients, but also SDF-1, HGF and VEGF used alone, have a strong pro-metastatic effect on CRL-1739 cells. We also demonstrated that the concentration of these cytokines is specifically elevated in the sera of patients in an early stage of malignancy. Our results indicate that SDF-1, HGF and VEGF are very important molecules involved in gastric cancer progression.